Damages for the injured patient: For private treatment and care or public treatment and care?. (January 2020) - Samuels, Alec
Should the basis of the law of damages or compensation for medical negligence be changed or reformed from the basis of private treatment and care to the basis of public treatment and care? This would remove the privilege of the claimant, still secure and safeguard him as a social casualty and save the National Health Service some money. However, the claimant would feel that he was being unjustly compensated.